Characteristics of Silkworm Population Growth (Tubifex sp.) at an Average Temperature of 27 °C - Fajri Mashudi; Azwar Thaib; Nurhayati Nurhayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Silkworms are one of the live feeds given to larvae in the hatchery phase because they have a high nutritional content. Silk worms are relatively small in size that fit into the non-larval mouth so they are easy to digest and easy to catch because of their slow movements. However, the availability of silk worms is still very limited and still relies on nature. So it is necessary to do further culture. Silkworm cultivation is influenced by the food source for growth. In addition to aspects of food, silk worms are also influenced by ecological factors such as temperature. This study aims to determine the characteristics of silkworm population growth (Tubifex sp.) at an average temperature of 27 0C. Data analysis used in this research is descriptive qualitative. The treatment used is at an average temperature of 270C. Based on the research, the highest peak population of silk worms ( Tubifex sp.) was obtained at 27,450C. with an average population of 3060 ind/cm2 and the lowest number of silk worms was found at 27.040C 2477 ind/cm2. The results showed that population growth at 27.450C provided the maximum number of silkworm populations.